2017
DOI: 10.7150/ijms.19553
|View full text |Cite
|
Sign up to set email alerts
|

Rhododendron oldhamii leaf extract improves fatty liver syndrome by increasing lipid oxidation and decreasing the lipogenesis pathway in mice

Abstract: Some members of Rhododendron genus are traditionally used as medicinal plants for arthritis, acute and chronic bronchitis, asthma, pain, inflammation, rheumatism, hypertension and metabolic diseases. To the best of our knowledge, there is no report on the protective effects of R. oldhamii leaf extract on non-alcoholic fatty liver disease (NAFLD) in vivo and in vitro. In this study, the effects of R. oldhamii leaf extract on inhibiting the free fatty acid (FFA)-induced accumulation of fat in HepG2 cells and on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Many researchers have conducted experiments on plant extracts and single compound isolated from extracts using various NAFLD models. Among them, the plant extracts studied were as follows: the lemon balm extract ALS-L1023, Vitex Agnus-Castus L. (Verbenaceae), volatile oil, mulberry leaf, licorice root, Uncaria tomentosa, Rubus crataegifolius roots, Lycium barbarum, and white button mushroom (WBM) [32] [19,[33][34][35][36][37][38]. Many single compound including flavonoids, alkaloids, polysaccharides, quinones, terpenes, coumarins, lignans, saponins, cardiac glycosides, phenolic acids, and amino acids have been shown to have considerable therapeutic effects on NAFLD [13,15,19,39].…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have conducted experiments on plant extracts and single compound isolated from extracts using various NAFLD models. Among them, the plant extracts studied were as follows: the lemon balm extract ALS-L1023, Vitex Agnus-Castus L. (Verbenaceae), volatile oil, mulberry leaf, licorice root, Uncaria tomentosa, Rubus crataegifolius roots, Lycium barbarum, and white button mushroom (WBM) [32] [19,[33][34][35][36][37][38]. Many single compound including flavonoids, alkaloids, polysaccharides, quinones, terpenes, coumarins, lignans, saponins, cardiac glycosides, phenolic acids, and amino acids have been shown to have considerable therapeutic effects on NAFLD [13,15,19,39].…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxicity was determined by the MTT assay using previously described method [ 20 ]. HepG2 cells (8000 cells/well) were seeded onto a 96-well plate and incubated for 24 h to allow cell adherence.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Recent study reported that quercitrin containing extract of Chrysobalanusicoco leaves inhibited fat accumulation in HFD-fed mice (36). Also, quercitrin isolated from Rhododendron oldhamii leaf extract improves fatty liver syndrome via increase of lipid oxidation and decrease of lipogenesis (37). Thus, quercitrin may be one of the compounds that contribute to the anti-obesity effect of CIEE.…”
Section: Ciee (Mg/kg) -----------------------------------------------mentioning
confidence: 98%